Data Communications and Network Security - H. Carr Houston (Mc Graw-Hill, 2006)
Written for students and managers who do not have a technical background, Data Communications and Network Security comprehensively introduces students to the technology and management of data communications. This includes both wired and wireless technology as well as comprehensive coverage of network security, helping both the organization and the individual create and maintain a data-safe environment. The book's unique organization allows the material to be presented in a variety of ways, making the book a strong match to any teaching approach.